High Permeate Recovery for Concentrate Reduction by Integrated Membrane Process in Textile Effluent. (1st September 2016) - Sudhakar, M.; Vijayalakshmi, P.; Nilavunesan, D.; Thiruvengadaravi, K.V.; Baskaralingam, P.; Sivanesan, S.
ABSTRACT: : The textile dyeing industry consumes a significant amount of high‐quality water for processing, which stresses water resources. In recent decades, technologies have been developed to recover water from wastewater. This study describes the high recovery (greater than 92%) of reusable water from an industrial‐scale hosiery dye‐water recovery facility, consisting of three stages of reverse osmosis and ultrafiltration. The effluent was pre‐treated before the membrane process was performed to prevent biofouling. The process performance results in the generation of a consistent water quality that is required for dyeing operations. An average feed flux of 15 l/m 2 h was maintained in the reverse osmosis membrane by regular chemical dosing and cleaning. The integrated membrane process achieved a permeate with a pH of 6.5 and total dissolved solids (TDS) of 160 mg/l, with no other contaminants, which is of sufficient quality for reuse in the cotton hosiery dyeing process.